2017
DOI: 10.1177/0972150916668620
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Social Influence and Green Consumption Values on Purchase Intention of Organic Clothing: A Study on Collectivist Developing Economy

Abstract: The present study is an attempt to investigate the impact of green consumption values and social influence on purchase intention for organic clothing. Five hypotheses were developed with the support of relevant literature. These were tested with the help of primary data of young adult Indian consumers in the age group 20–40 years, collected through a structured questionnaire. Structural equation modelling (SEM) was used to test the hypotheses. The results of structural model revealed that attitude partially me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
101
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(117 citation statements)
references
References 60 publications
14
101
0
2
Order By: Relevance
“…The study's results revealed that consumers' ATT had a significant positive impact on the PI for vegetarian burgers (β = 0.174, p < 0.001); thus, H1a is valid; that is, when consumers think that vegetarian burgers are healthy or they themselves possess environmental and social responsibilities, they have a more positive attitude toward vegetarian burgers and are more likely to buy them. This result is consistent with that of previous studies [25,54,56,57]. Second, the study results revealed that consumers' SNs had no significant relationship with the PI for vegetarian burgers (β = 0.440, p > 0.05), therefore H1b is not tenable; that is, consumers will not buy vegetarian burgers because of the opinions of their family members, friends, and colleagues.…”
Section: Hypothesis Testingsupporting
confidence: 91%
See 1 more Smart Citation
“…The study's results revealed that consumers' ATT had a significant positive impact on the PI for vegetarian burgers (β = 0.174, p < 0.001); thus, H1a is valid; that is, when consumers think that vegetarian burgers are healthy or they themselves possess environmental and social responsibilities, they have a more positive attitude toward vegetarian burgers and are more likely to buy them. This result is consistent with that of previous studies [25,54,56,57]. Second, the study results revealed that consumers' SNs had no significant relationship with the PI for vegetarian burgers (β = 0.440, p > 0.05), therefore H1b is not tenable; that is, consumers will not buy vegetarian burgers because of the opinions of their family members, friends, and colleagues.…”
Section: Hypothesis Testingsupporting
confidence: 91%
“…Ajzen believed that ATT is an evaluation criterion composed of the sum of an individual's behavioral beliefs and outcome evaluations [44,52]. Studies have revealed that ATT toward organic foods [53,54] and green products [21,46,[55][56][57] have an impact on consumers' PI. Therefore, this study postulates that consumers' attitudes toward artificial meat products will have an impact on their PI; thus, H1a is as follows: ATT has a significant positive impact on the intention to purchase artificial meat products.…”
Section: Theory Of Planned Behavior (Tpb)mentioning
confidence: 99%
“…It indicates that individual behavior is driven by behavioral intentions, which are a function of three independent constructs (i.e., attitude toward behavior, subjective norms, and perceived behavioral control) [18]. It has been widely used and extended in many studies, such as new system adoption behavior [19], e-service usage [20], oil palm smallholder planters' intention [21], microblogging intention [22], and purchase intention for organic clothing [23] and energy-efficient appliances [24].…”
Section: Theory Of Planned Behaviormentioning
confidence: 99%
“…Green consumption value occurs when an individual’s purchase and consumption behaviour reflects respect for the environment (Haws et al, 2014; Kottala & Singh, 2015; Moser, 2016; Nguyen et al, 2016). In other words, green consumption value refers to an individual’s desire to consume only those food products that meet their environmental and sustainability expectations (Patterson & Spreng, 1997; Varshneya et al, 2017; Wu & Chen, 2014). The green consumption values highly govern green consumer behaviour such that they purchase more green products (Kim & Moon, 2012; Nguyen et al, 2016).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…The green consumption values highly govern green consumer behaviour such that they purchase more green products (Kim & Moon, 2012; Nguyen et al, 2016). These consumers are well aware that their purchase patterns will not harm the environment (Varshneya et al, 2017; Wang & Lin, 2017).…”
Section: Hypothesis Developmentmentioning
confidence: 99%